The Microbial Metagenome of Eluates Obtained From the Surface of Broccoli Heads Subjected to Different Light Treatments - Zeng, Shixian; Cui, Jingchun; Xiong, Jinliang; Yuan, Shuzhi; Yue, Xiaozhen; Guan, Wenqiang; Gao, Lipu; Liu, Jia; Zuo, Jinhua; Wang, Qing (Frontiers in Microbiology, 2022)
Foodborne illnesses present a major threat to public health and are frequently attributed to foodborne pathogens present on fresh produce. Some opportunistic pathogens of broccoli are also responsible for causing head rot. Three different light treatments, UV-C, red LED(50 μmL/m2/s), and UV-C+LED combined were used to treat broccoli prior to or during storage. Following the light treatments, microorganisms present in eluates obtained from the surface of broccoli were characterized using a metagenomic approach. Metagenomic DNA libraries were subjected to high-throughput sequencing on an Illumina Hiseq platform. Results indicated that the compound treatment of LED red light and UV-C had the best sensory preservation effect on broccoli, followed by LED red light and UV-C. And the bacterial communities in the eluates obtained of from all three light treatments were primarily represented at the phylum level by Proteobacteria and Firmicutes, while fungal communities were primarily represented by Ascomycota and Basidiomycota. Further analysis of the data indicated that the three different light treatments all reduced the presence of most foodborne pathogens and bacterial taxa responsible for broccoli spoilage. While UV-C has a significant inhibitory effect on Botrytis cinerea, the light treatments increased the relative abundance of Pseudomonas fluorescens. Results indicate that a metagenomic approach can be used to detect pathogenic bacteria and fungi on fresh vegetables and assess the impact of management practices, such as light treatments, designed to maintain postharvest quality, on the composition of the microbiome present on the surface of harvested produce.